“Because migration begins from the villages”: environmental change within the narrations of the Ewe diaspora - Felicitas Hillmann; Rueben Korley Okine; Giulia Borri (Ethnic and Racial Studies, 2020)
The article analyses the role of environmental change within the narrations of the Ewe-diaspora, a sub-group of the Ghanaian diaspora. It focusses on the role and the impact of the diaspora when it comes to coping with environmental change at the place of origin. It highlights the nexus with international migration.
Keywords: 710; Diaspora; Environmental Change; Migration; Ghana; Livelihoods